2018
DOI: 10.1190/geo2017-0534.1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental identification of the transition from elasticity to inelasticity from ultrasonic attenuation analyses

Abstract: The transition from recoverable elastic to permanent inelastic deformation is marked by the onset of fracturing in the brittle field. Detection of this transition in materials is crucial to predict imminent failure/fracturing. We have used an ultrasonic pulse transmission method to record the change in waveform across this transition during fracturing experiments. The transition from elastic to inelastic deformation coincides with a minimum in ultrasonic attenuation (i.e., maximum wave amplitude). Prior to thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 65 publications
(96 reference statements)
3
12
0
Order By: Relevance
“…This can be further confirmed from the near‐linear relationship between the ε NE AT and the ultrasonic wave amplitude above the CI (Figure b), coherent with the findings of Wulff et al (). This observation is consistent with the studies of Wulff et al (), Couvreur et al (), and Barnhoorn et al (), who found that the changes in ultrasonic signals can be an objective signature of onset (not a precursor) of microcracking in rocks where the damage is diffuse (randomly distributed) and small relative to the ultrasonic wavelength (identical to the scenario in the present study).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…This can be further confirmed from the near‐linear relationship between the ε NE AT and the ultrasonic wave amplitude above the CI (Figure b), coherent with the findings of Wulff et al (). This observation is consistent with the studies of Wulff et al (), Couvreur et al (), and Barnhoorn et al (), who found that the changes in ultrasonic signals can be an objective signature of onset (not a precursor) of microcracking in rocks where the damage is diffuse (randomly distributed) and small relative to the ultrasonic wavelength (identical to the scenario in the present study).…”
Section: Resultssupporting
confidence: 94%
“…The results in present work show that the amplitudes drop by 40%–80% from their initial value over the course of loading (Figure ). This observation is consistent with the conclusions of several other studies that attenuation is sensitive to flaws in the medium through which a wave propagates (Barnhoorn et al, ; Gowd, ; Gupta, ; Lockner et al, ; Modiriasari et al, ; Rao & Raman, ; Walsh, ). This is also consistent with the fact that at high frequencies (in the range of MHz) the ultrasonic wave amplitude is more sensitive to damage than the ultrasonic wave velocity (Barnhoorn et al, ; Chen et al, ; Modiriasari et al, ; Pyrak‐Nolte et al, , Pyrak‐Nolte & Cook, ; Pyrak‐Nolte et al, , ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Monitoring the evolution of a rock matrix towards dynamic failure with a wavelet at the mesoscopic scale (Li et al, 1998;Heap and Faulkner, 2008;Barnhoorn et al, 2010Barnhoorn et al, , 2018, is characterised by the continuous evolution of its wavefield propagation properties. For Unconfined Compressive Strength tests this can be illustrated by considering the different stages of material deformation as shown in figure 2 for the BNT1 core sample.…”
Section: Cwi and Cwd Monitoring Of An Ucs Testmentioning
confidence: 99%